Penerapan Model The Learning Cell dalam Pembelajaran Pendidikan Agama Islam di Kelas VII SMP Muhammadiyah 07 Sukaraja - Risanti, Amelia; Fatoni, M (JUPIN (Jurnal Pendidikan Islam Nusantara), 2022)
The main problem that occurs in the learning process is learning that is less effective, less efficient, and less passionate about learning which causes low student motivation, learning awareness and seriousness in learning, so that mastery of learning materials is not fulfilled. Therefore, appropriate learning strategies and learning resources are needed so that problems can be resolved. The research method uses a qualitative descriptive approach. The research subjects are Islamic religious education teachers and students of SMP Muhammadiyah 07 Sukaraja. The results of the study show that: 1) The application of the learning cell model in learning Islamic religious education is very good, because this method can motivate and develop the potential of students in learning. 2) Learning outcomes by applying the learning cell model are greatly improved, it can be seen that students can easily understand Islamic religious education learning materials. 3) The advantage of applying the learning model is that students are able to develop and quickly understand Islamic religious education learning materials. it can be concluded that there is a very good change by using the learning cell model.